Analysis of Smartphone Camera Stabilization Based on Gyroscope Using Exponential Smoothing in Mobile Applications - Suci Lestari MS; Tito Pinandita; Dimara Kusuma Hakim (Jurnal E-Komtek, 2026)
Camera usage on mobile devices under dynamic conditions frequently induces vibration (jitter) and unstable orientation changes. This study aims to analyze the effectiveness of the Exponential Smoothing method in reducing rotational fluctuations of a gyroscope-based smartphone camera in a mobile application. An experimental approach was employed across six movement scenarios, namely stationary conditions, slow movement, fast movement, walking, stair climbing, and vehicle riding, by measuring rotation angle values and jitter values before and after stabilization. The results indicate a significant reduction in jitter following the application of Exponential Smoothing across all testing scenarios. The gyroscope-based stabilization system utilizing this method is proven effective in improving smartphone camera rotation stability in mobile applications.